If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -11x = 0 Combine like terms: 15x + -11x = 4x 4x = 0 Solving 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '4'. x = 0 Simplifying x = 0
| 2c-1=-15 | | (3x-2)^2=(1/4) | | X/-4-10=-2 | | .50x=90 | | 7(2n-4)=(7n+7)+6 | | (2a^-2b^4)^3b/(10a^3b^2) | | -3ab(2a^2+4b+3c)= | | 42-y=39 | | z/1=16 | | 9(2n-4)=(3n+8)+6 | | 2(x+1)-3(x-2)=x-2 | | 36=12/x | | 3x=(x+8)(x-4) | | 2z^3-6z^2-920=0 | | 10x-18x=4 | | 21+y=17 | | 14w=91. | | 3ex-1=75 | | y=-6(x-18) | | 3u-12=12 | | .5x+2.5=-6 | | 6x-11=61-3x | | 13x+3=-23 | | y+8=28 | | 5x+12=3x+13 | | z+6=15 | | 3x+27=12x+13 | | 7x-2=6x+1 | | 360=127+53+127+-2+5x | | y/2=2 | | (-10x-7)-(3x-10)= | | (10x-7)-(3x-10)= |